Práticas educativas maternas e empatia em crianças de baixa renda - SANTOS, Lorena Ribeiro dos (Universidade Federal do Pará, 2019)
The present study investigated the educational practices and parenting styles prevalent in mothers of low-income children and the relationship of these practices with the empathy of children. The research included the participation of 36 children, 9-11 years old, and their mothers. It was used as instruments the Sociodemographic Questionnaire, the Parental Styles Inventory and the Scale of Empathy for Children and Adolescents. The results indicate that scores of children's responses, regarding childrearing practices, were significantly lower than the scores of mothers, with a prevalence of negative practices in both perspectives. The parenting style is the predominant risk and below-average regular. It is found that higher levels of education of the children are related to higher levels of empathy. There is no correlation between maternal educational practices and levels of empathy. This study raised important information regarding childrearing practices, as the prevalence of negative practices in the surveyed mothers. The detection of this deficit raises the need for more comprehensive research on educational practices in low-income mothers, and the development of guidance and intervention programs that help mothers and fathers in the education provided to children.